An Improved RFID-Based Localization Algorithm for Wireless Sensor Networks - Ayong Ye; Yuanjing Ling; Li Xu; Xiaoliang Yang (International Journal of Distributed Sensor Networks)
The position of RFID-tagged objects in sensor networks is becoming an important feature for ubiquitous computing applications. In this work, we develop an improved positioning algorithm for RFID-tagged objects. Compared with the VIRE algorithm, we apply a nonlinear interpolation method to further improve the positioning precision. We also introduce the concept of credibility of reference tags to reduce the influence of abnormal tags on positioning precision. Finally, we provide detailed simulations to evaluate the proposed technique.